How Do Shocks Affect Enrollment in Faith-Based Schools? : Evidence from West Africa - Elmallakh, Nelly; Wodon, Quentin (Taylor and Francis, 2022)
The COVID-19 pandemic has renewed concerns about how shocks may affect religious and other private schools in low-income countries, especially when they do not benefit from state support. By reducing parental incomes, shocks – not only epidemics but also natural disasters and conflicts, reduce overall enrollment in school. But they may also lead to a shift from private to public schools with potentially differentiated effects by type of private school depending on context. In addition, household responses to shocks such as migration may lead to a change in the socio-cultural context in which households live, and these changes may also affect school choice. This paper explores the effects of shocks and migration on school choice in West Africa. Results suggest that shocks and migration lead to a shift from private to public schools, but with differentiated effects by type of private schools.